Les formations quaternaires du Bassin de Huancayo et leur néotectonique (Andes Centrales Péruviennes) - Dollfus, Olivier (1968)
In the Huancayo-Jauja intra-Andean basin, whose origin seems to be linked to a warping of the «Puna» tertiary erosion surface, an important set of quaternary formations was deposited. The oldest one is the «Jauja» lacustrine formation; the following ones constitute t', t'' and t''' terraces, each one of them being contemporaneous with one glaciation stage. New observations allow to prove that the «Jauja » and t''' formations have been folded, generating a System of narrow anticlinal ripples as also large, flat synclinal basins. The terraces sedimentation and the deepening of the rio Mantaro gorges below the basin were also partly conditioned by a block tectonics which appears to continue at the present time. These new facts are then replaced into the frame of the basin and of the area climatic evolution, in the Quaternary.